An analysis on the information behavior and social support network of foreign students during their settlement process in the University of the Philippines Diliman - Mondarte, Nissi A.
Studying outside of one’s home country is not an easy and smooth transition. Different challenges accompany the preparation process. This paper discusses on how foreign students seek and acquire information, presence of dominant information process, and the role of social support network during their settlement period. The study collected a total of 17 survey questionnaire response out of the 20 emailed participants. In addition, five participants were given follow-up interview questions. The data were analyzed using descriptive analysis, cross tabulation method and content analysis. Findings of the study include (1) detailed preference of information needs, practices on information acquisition and retrieval processes (2) dominance of chosen information strategies and sources on information horizon (3) social support networks’ role in contributing to adjustment and acculturation. Implications of the study are discussed to provide an insight and perception on the foreign students’ information behavior and promote feelings of social inclusion in the community.